Frequency of H-pylori Stool Antigen in Patients with Perforated Duodenal Ulcer Disease (Medical Forum Monthly, 2024)
Objective: To find the frequency of H-pylori stool antigen in patients with perforated duodenal ulcer disease.Study Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Department of General Surgery, Nishtar Hospital Multan from March 2016 to January 2017.Materials and Methods: A total number of three hundred and seventy eight patients were enrolled. Data was analyzed with a statistical software SPSS version 23. All numerical variables were calculated as mean ± SD and categorical variables were calculated as frequency and percentages. Chi square test was applied to see the effect modification and p value ≤0.05 was accepted as significant.Results: Total number patients included in this study were three hundred and seventy eight (378) in which 237(62.7%) were male with mean age 44.75 ± 8.46 and 141(37.3%) were females with mean age 44.89 ± 9.93. From these 378 patients,200 (52.9%) patients having H-Pylori antigen and in 178 (47.1%) patients H-Pylori antigen was absent.Conclusion: It is concluded that patient with perforated duodenal ulcer are at high risk of Helicobacter pylori infection, so the case of perforated duodenal ulcer should be investigated more aggressively. Early diagnosis can save the patient from dangerous effects of H-pylori infection.